Transformation of Islamic Education through the Integration of Sufism For the Enhancement of Spiritual Intelligence - Sudin, Mahmudin; Zailani, Zailani (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
Islamic education faces a significant challenge in the Society 5.0 era, where the dominance of cognitive approaches often fails to address the critical need for students' spiritual strengthening. This situation creates an urgent demand for more holistic educational models grounded in Sufi principles. This study aims to map the development of research on the integration of Sufism into Islamic education and its contribution to enhancing spiritual intelligence. A Systematic Literature Review (SLR) was employed to analyze scholarly literature from 2000 to 2024, following the stages of research question formulation, selection criteria establishment, cross-database searching (international and national), article screening, data extraction, and thematic analysis. The synthesis of findings reveals that Sufi values—such as contemplation (tafakkur), soul purification (tazkiyah), and character building—significantly strengthen curriculum design, learning strategies, and student transformation. This integration has been proven to foster the development of spiritual, cognitive, and emotional intelligence as the foundation for cultivating the complete human (insan kamil). The study's implications underscore the necessity of developing more humanistic, adaptive, and holistic-oriented Islamic education models to navigate the complexities of the digital age.